2017
DOI: 10.1016/s1473-3099(17)30394-8
|View full text |Cite
|
Sign up to set email alerts
|

Trends in antimicrobial resistance in bloodstream infection isolates at a large urban hospital in Malawi (1998–2016): a surveillance study

Abstract: SummaryBackgroundBacterial bloodstream infection is a common cause of morbidity and mortality in sub-Saharan Africa, yet few facilities are able to maintain long-term surveillance. The Malawi-Liverpool-Wellcome Trust Clinical Research Programme has done sentinel surveillance of bacteraemia since 1998. We report long-term trends in bloodstream infection and antimicrobial resistance from this surveillance.MethodsIn this surveillance study, we analysed blood cultures that were routinely taken from adult and paedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
259
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(294 citation statements)
references
References 43 publications
27
259
7
1
Order By: Relevance
“…The high AMR frequencies for first-line drugs, in particular penicillins, detected in this study are similar to reports of other intestinal, extra-intestinal and environmental isolates of E. coli 22,37 . Of note, the high levels of ciprofloxacin-resistance found in this study at the Asian sites corresponded to high levels reported in clinical cases in India, Bangladesh and Pakistan 17,18,21,23,24,38 . Further, while ESBL-producing aEPEC were detected in this study in Asia, the frequency of these was lower than those reported from hospitals in both Asia and Africa 18,21,31,38 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The high AMR frequencies for first-line drugs, in particular penicillins, detected in this study are similar to reports of other intestinal, extra-intestinal and environmental isolates of E. coli 22,37 . Of note, the high levels of ciprofloxacin-resistance found in this study at the Asian sites corresponded to high levels reported in clinical cases in India, Bangladesh and Pakistan 17,18,21,23,24,38 . Further, while ESBL-producing aEPEC were detected in this study in Asia, the frequency of these was lower than those reported from hospitals in both Asia and Africa 18,21,31,38 .…”
Section: Discussionsupporting
confidence: 83%
“…Of note, the high levels of ciprofloxacin-resistance found in this study at the Asian sites corresponded to high levels reported in clinical cases in India, Bangladesh and Pakistan 17,18,21,23,24,38 . Further, while ESBL-producing aEPEC were detected in this study in Asia, the frequency of these was lower than those reported from hospitals in both Asia and Africa 18,21,31,38 . These findings suggest the prevalence of ESBLs, and indeed resistance to carbapenems and last-line aminoglycosides (which were not detected in these community aEPEC) are in higher circulation in hospital settings and have not yet become established in the community settings we investigated.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Resistance has soared, according to a surveillance study in adults and paediatric patients by the Malawi Liverpool Wellcome Centre, the research institute next to Queen Elizabeth hospital 1. Over 18 years to 2016, although the number of bloodstream infections fell, the proportion involving resistant bacteria increased, says Nicholas Feasey, an infectious diseases researcher who led the study.…”
Section: Resistance To Stocked Antibioticsmentioning
confidence: 99%
“…Outbreaks of severe acute respiratory syndrome, pandemic influenza A H1N1, Ebola virus (EBOV), and Zika virus have prompted international responses, whereas influenza A H7N9 and H5N1, Lassa fever virus, Nipah virus, and Middle East respiratory syndrome coronavirus, among other agents, have been a source of regional concern. The incidence and endemic range of "neglected" infections, including dengue and cholera (16,17), have expanded, and antimicrobial resistance has threatened to derail the control of tuberculosis, typhoid, malaria, gonorrhea, yaws, and invasive bacterial infections (18)(19)(20)(21)(22)(23). Although highly effective vaccines are available, measles and yellow fever have resurged on multiple continents, due to gaps in vaccine coverage (24,25), while short-lived vaccine-induced protection has facilitated unexpected resurgences in diseases once on the path to elimination, such as pertussis and mumps (26,27).…”
mentioning
confidence: 99%